Comments on "Association of excessive mobile phone use during pregnancy with birth weight: an adjunct study in Kumamoto of Japan Environment and Children's Study" - Ghazal Mortazavi; S.A.R. Mortazavi; S.M.J. Mortazavi (Komiyama Printing Co. Ltd, 2017)
Abstract We have read with interest the article by Lu et al. entitled "Association of excessive mobile phone use during pregnancy with birth weight: an adjunct study in Kumamoto of Japan Environment and Children's Study" published recently in the Environmental Health and Preventive Medicine. Although this paper addresses a very challenging issue, it has some shortcomings. Mortazavi et al. have previously studied the effects of ionizing and non-ionizing radiation on birth weight of newborns and found no statistical significant differences between the mean weight of newborns whose mothers had been exposed to electromagnetic fields (EMF) generated by mobile phones and those of non-exposed mothers. The study performed by Lu et al. cannot answer this very key question that whether ordinary use of mobile phone during pregnancy can lead to low birth weight. The origin of the controversy between the findings of these two studies and the shortcomings of the article by Lu et al. are discussed.